Deposit guarantee schemes : a European perspective - Arnaboldi, Francesca; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
Arnaboldi highlights the importance of one of the three pillars of the Banking Union, the common mechanism for insuring deposits. She claims that integrated financial markets require a European solution with regard to deposit insurance and that the establishment of a pan-European scheme could address the problems for large cross-border banks.
Keywords: Finance; Banks and banking; Investment banking; Securities